Pengaruh Debt to Equity Ratio dan Price to Earning Ratio terhadap Nilai Perusahaan (Studi pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Fadhia Nurhalizah; Indri Utami; Tamy Ali Januarti (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2026)
This study aims to determine the effect of Debt to Equity Ratio (DER) and Price to Earning Ratio (PER) on firm value. The population in this study consisted of 44 food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2025 period, while the sample was determined using the purposive sampling technique with a total sample of 11 companies. This study used and implemented descriptive and verificative research methods with a quantitative approach. The analytical method used in this research was panel data regression analysis using the Eviews program. The results of this study indicate that the Debt to Equity Ratio (DER) does not have a significant effect on company value, while Price to Earning Ratio (PER) has no significant effect on company value. This research faced data constraints that resulted in having to select samples based on the availability of complete corporate financial reports across specific periods. The scope should be expanded by including other variables that are believed to have a greater influence on company value.